Relationship between Liquidity, Volatility and Trading Activity: An Intraday Analysis of Indian Stock Market - Cheriyan, Namitha K.; Daniel, Lazar (International Journal of Economics and Financial Issues, 2019)
The liquidity crunch arising out of volatile market conditions is a significant concern for investors across the globe. The trading activity in the market is an important attribute determining the liquidity as well as the volatility of any stock market. Given this triangular relationship, this study analyzes the relationship between liquidity, volatility and trading activity in the Indian stock market. Employing OLS regression estimates, the study identifies a contraction in liquidity in response to greater trading activity which is found to be increasing volatility in the market. It finds that higher volatility in Indian market is associated with greater illiquidity in the market. Even after adjusting for the impact of trading activity, volatility is found to be exhibiting a statistically significant impact on liquidity. Keywords: Indian stock market, intraday liquidity, OLS regression, trading activity, volatility JEL Classifications: C1, G11, G12 DOI: https://doi.org/10.32479/ijefi.7268